Rekonstruksi Kebijakan Penganggaran Sisa Lebih Perhitungan Anggaran (SiLPA) Dana Otonomi Khusus di Kabupaten Yalimo Provinsi Papua - gasper liauw (Institut Pemerintahan Dalam Negeri, 2019)
The implementation of the budgeting policy, the rest of previous year’s budget calculation from the special autonomy fund in Yalimo district has not been supported by special regulations. The delay in the submission of technical instructions resulted in the swelling of this budget in the regional treasury. The result obtained are first, the implementation of the spcial autonomy budget budgeting policy is not in accordance with the principles and policies of asymetric decentralization budegeting;secondly, the Minister of Home Affairs number 13 of 2006; thirdly, the reconstruction of special autonomy budgeting policy refers to government policies conducted for special allocation funds for teacher professional allowances